IoT Based Health Monitoring System for Obese Children - Ratnadurai, Dhakshyani; A. Deneshwar (Journal of Advanced Mechanical Engineering Applications, 2025)
Childhood obesity continues to be a serious global health issue with far-reaching effects on people's lives and societies. The development, deployment, and evaluation of OBISENSE, an innovative solution created to address the challenges associated with handling children obesity, are presented in this research. OBISENSE is an IoT-based health monitoring system. The system's architecture combines health science and IoT technology to deliver precise and immediate measures of height, weight, and heart rate. The OBISENSE system uses these parameters to calculate Body Mass Index (BMI) and assess obesity status, making it an essential tool for evaluating and controlling childhood obesity. The OBISENSE system provides a simple-to-use mobile application that encourages users to take an active role in their journey towards better health. Individuals may easily track their health measurements with the app, access previous data, and get personalised suggestions for leading a healthy lifestyle. A better user experience is ensured by the system's design, which places an emphasis on usability, accessibility, and compatibility with current technological platforms. The OBISENSE system was put through extensive testing to confirm its functionality. In this project, through a variety of scenarios, including height, weight, and heart rate measurements with subsequent BMI estimations, the system's accuracy and dependability is assessed. The findings show that the OBISENSE system reliably delivers accurate and trustworthy health data, enabling efficient monitoring of paediatric obesity. The OBISENSE system is aware of its limitations, including changes in sensor accuracy and potential ambient influences on measurements.